2018
DOI: 10.1371/journal.pone.0196035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat type on intestinal digestibility of fatty acids, fatty acid profiles of breast meat and abdominal fat, and mRNA expression of lipid-related genes in broiler chickens

Abstract: A group of 240-day-old Ross cockerels were used in a 4-week experiment to assess the effect of the fat type on the intestinal digestibility of fatty acids (FAs), the FA profiles of breast meat and abdominal fat, and the mRNA expression of six hepatic lipid-related genes. Experimental diets were supplemented with rapeseed oil, pork lard or palm oil at 60 g/kg. In the control diet, wheat starch was substituted for the fat source. The highest ileal digestibility of the fat and all FAs (except stearic acid) was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
2
26
0
2
Order By: Relevance
“…It is well reported that dietary fats influence the fatty acid composition of meats and adipose tissues in broilers ( Crespo and Esteve-Garcia, 2001 , Londok et al., 2017 , Skřivan et al., 2018 ), incorporating diet-origin fatty acid into tissues. As expected, fatty acid profiles in the abdominal fat reflected those in dietary fat sources, and no age effect was noted which indicates that fatty acid composition of abdominal fat, once altered, maintained constant throughout the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…It is well reported that dietary fats influence the fatty acid composition of meats and adipose tissues in broilers ( Crespo and Esteve-Garcia, 2001 , Londok et al., 2017 , Skřivan et al., 2018 ), incorporating diet-origin fatty acid into tissues. As expected, fatty acid profiles in the abdominal fat reflected those in dietary fat sources, and no age effect was noted which indicates that fatty acid composition of abdominal fat, once altered, maintained constant throughout the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…Tan Choon-Hui et al [10] showed that the major saturated fatty acids (SFAs) in PO were palmitic (43.7%) and stearic (4.5%) acids, and the main unsaturated fatty acids (UFAs) were oleic (40.2%) and linoleic (9.6%) acids. PO is widely used in human and animal nutrition [11]. According to Skřivan et al [11], palm oil is a common supplement in poultry diets.…”
Section: Introductionmentioning
confidence: 99%
“…PO is widely used in human and animal nutrition [11]. According to Skřivan et al [11], palm oil is a common supplement in poultry diets. However, due to the negative impact on the environment, i.e., deforestation, extinction of endangered species and loss of biodiversity, as well as nutritional issues (high ratio of saturated fatty acids), consumers are looking for an alternative energy source [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many examples in the literature show that the fatty acid profiles of animal products (meat, eggs, etc.) can be manipulated with various oils and additives to the diet (Suksombat et al, 2006;Bostami et al, 2017;Kanakri et al, 2018;Skřivan et al, 2018). However, only a limited number of such studies used BCS and its oil.…”
Section: Tablementioning
confidence: 99%